2011
DOI: 10.1111/j.1872-034x.2011.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise improves insulin resistance and decreases body fat and serum levels of leptin in patients with hepatitis C virus

Abstract: Patients with CH-C could safely walk as aerobic exercise. Furthermore, walking improved insulin resistance and decreased body fat while lowering serum levels of leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
2
25
1
2
Order By: Relevance
“…There are several reports with similar findings; reporting the association between physical exercise and the plasma level of insulin and leptin (Konishi et al, 2011). Although investigators showed that lower concentrations of leptin and insulin stimulate appetite and energy intake and suppress energy expenditure (Benoit et al, 2004), the results of the current study demonstrated that there were significant decrease in BMI (P < 0.05), percent body fat (P < 0.01), waist circumference (P < 0.05) in obese subjects after 8 weeks exercise training and they were positively correlated with the decrease in plasma leptin level.…”
Section: Discussionsupporting
confidence: 48%
“…There are several reports with similar findings; reporting the association between physical exercise and the plasma level of insulin and leptin (Konishi et al, 2011). Although investigators showed that lower concentrations of leptin and insulin stimulate appetite and energy intake and suppress energy expenditure (Benoit et al, 2004), the results of the current study demonstrated that there were significant decrease in BMI (P < 0.05), percent body fat (P < 0.01), waist circumference (P < 0.05) in obese subjects after 8 weeks exercise training and they were positively correlated with the decrease in plasma leptin level.…”
Section: Discussionsupporting
confidence: 48%
“…No adverse events were seen in the intervention group [70]. Additionally, several studies have demonstrated that formalized exercise regimen will improve insulin sensitivity among patients with liver disease, which is particularly important among patients with sarcopenic obesity [71][72][73]. Further studies are necessary to further define the type and duration of exercises and their long-term effect on morbidity and mortality among chronic liver disease patients.…”
Section: Exercise and Preservation Of Muscle Massmentioning
confidence: 87%
“…Eizadi et al stated that prolonged aerobic exercise improved lipid profile, reduced insulin resistance and increased insulin sensitivity in obese patients (19). Also, Konishi et al applied a program of walking exercise for 15 patients with HCV and founded that aerobic exercises decreased body fat and improved insulin resistance (20). Similarly, Jiménez and Ramírez-Vélez found that eight weeks of strength training for obese subjects improved insulin sensitivity (21).…”
Section: Discussionmentioning
confidence: 99%